Invasion trajectory of alien trees: the role of introduction pathway and planting history - Jason E. Donaldson; Cang Hui; David M. Richardson; Mark P. Robertson; Bruce L. Webber; John R.U. Wilson (Global Change Biology, 2014)
Global change is driving a massive rearrangement of the world's biota. Trajectories of distributional shifts are shaped by species traits, the recipient environment and driving forces with many of the driving forces directly due to human activities. The relative importance of each in determining the distributions of introduced species is poorly understood. We consider 11 Australian Acacia species introduced to South Africa for different reasons (commercial forestry, dune stabilization and ornamentation) to determine how features of the introduction pathway have shaped their invasion history. Projections from species distribution models ( SDM s) were developed to assess how the reason for introduction influences the similarity between climatic envelopes in native and alien ranges. A lattice model for an idealized invasion was developed to assess the relative contribution of intrinsic traits and introduction dynamics on the abundance and extent over the course of simulated invasions. SDM s show that alien populations of ornamental species in South Africa occupy substantially different climate space from their native ranges, whereas species introduced for forestry occupy a similar climate space in native and introduced ranges. This may partly explain the slow spread rates observed for some alien ornamental plants. Such mismatches are likely to become less pronounced with the current drive towards ‘eco gardens’ resulting in more introductions of ornamental species with a close climate match between native and newly introduced regions. The results from the lattice model showed that the conditions associated with the introduction pathway (especially introduction pressure) dominate early invasion dynamics. The placement of introduction foci in urban areas limited the extent and abundance of invasive populations. Features of introduction events appear to initially mask the influence of intrinsic species traits on invasions and help to explain the relative success of species introduced for different purposes. Introduction dynamics therefore can have long‐lasting influences on the outcomes of species redistributions, and must be explicitly considered in management plans.